A preliminary study of human paraoxonase and PON 1 L/M 55-PON 1 Q/R 192 polymorphisms in Turkish patients with coronary artery disease - Kaman, Dilara; Ilhan, Necip; Metin, Kerem; Akbulut, Mehmet; Ustundag, Bilal (John Wiley & Sons Ltd, 2009)
Paraoxonase 1 (PON 1) is a high-density lipoprotein (HDL)-associated enzyme with antioxidant function protecting low-density lipoprotein (LDL) from oxidation. PON 1 has two amino acid polymorphisms in coding region; L/M 55 and Q/R 192. These polymorphisms modulate paraoxonase activity of the enzyme. PON 1 activity decreases in coronary artery disease (CAD). In the present study, distribution of PON 1 L/M 55 and Q/R 192 polymorphisms and the effect of these polymorphisms on the activities of PON 1, and on the severity of CAD in 277 CAD (+) patient and 92 CAD (-) subjects were examined. PON 1 L/M 55 and Q/R 192 genotypes were determined by PCR, RFLP and agarose gel electrophoresis techniques. Genotype distributions and allele frequencies for PON 1 Q/R 192 polymorphism were not significantly different between controls and CAD (+) patient group (p > 0.05), but in genotype and allele distribution of PON 1 L/M55 polymorphism, there was significantly difference among groups (p < 0.05). Genotype distributions for both polymorphisms were not significantly different between subgroups of single-vessel disease (SVD), double-vessel disease (DVD) and triple-vessel disease (TVD). Serum PON 1 activity was lower in CAD (+) group than in controls and this was also statistically significant (p < 0.001). In both groups, the highest PON activities were detected in LL and RR genotypes. In summary, our results suggest that there is an association between the PON 1 L/M 55 polymorphism of paraoxonase and CAD in Turkish patients but not with PON 1 Q/R 192 polymorphism. However, it is hard to correlate these polymorphisms and severity of CAD. Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: paraoxonase; coronary artery disease; polymorphism